An attack against them all? drivers of decisions to contribute to NATO collective defense - Binnendijk, Anika; Priebe, Miranda (RAND Corporation, 2019)
Russia's 2014 annexation of Crimea and military operations in Eastern Ukraine have prompted renewed discussion about the possibility of a Russian attack on a North Atlantic Treaty Organization (NATO) ally, particularly in the Baltics. Many analysts have raised questions about whether NATO members would respond militarily to such an attack. This report contributes to U.S. defense planning by identifying 13 key factors that are likely to affect each member's decision to participate in a military response to either an unconventional or conventional Russian attack. Based on this analysis, the report recommends ways to reduce allies' vulnerability to Russian influence and increase alliance cohesion
Keywords: North Atlantic Treaty Organization / Armed Forces; North Atlantic Treaty Organization / Decision making; North Atlantic Treaty Organization; Armed Forces; Decision making